Beethoven's theatrical quartets opp. 59, 74, and 95 - November, Nancy ca. 20./21. Jh (Music in context, 2013)
Beethoven's middle-period quartets, Opp. 59, 74 and 95, are pieces that engage deeply with the aesthetic ideas of their time. In the first full contextual study of these works, Nancy November celebrates their uniqueness, exploring their reception history and early performance. In detailed analyses, she explores ways in which the quartets have both reflected and shaped the very idea of chamber music and offers a new historical understanding of the works' physical, visual, social and ideological aspects. In the process, November provides a fresh critique of three key paradigms in current Beethoven studies: the focus on his late period; the emphasis on 'heroic' style in discussions of the middle period; and the idea of string quartets as 'pure', 'autonomous' artworks, cut off from social moorings. Importantly, this study shows that the quartets encompass a new lyric and theatrical impetus, which is an essential part of their unique, explorative character